Music & dance, a rich culture [videorecording (DVD)]. (Bennett Watt HD Productions, 2011)
Irish traditions are celebrated with passion and energy in a land where music and dance is as much a part of the culture as shamrocks and leprechauns. The tour begins in Kilrush at Mrs. Crotty's music festival then travels around the country to sample a wide variety of great Irish music & dance. Points of interest include: Cliffs of Moher, Bru Boru Step Dancing, Kilkenny Street Musicians, Melody's Pub, Belfast Trio, and Raithcairn Gaelic Traditions.